Transport Prices and Costs in Africa : A Review of the International Corridors - Teravaninthorn, Supee (Washington, DC : World Bank, 2012)
The objective of the study is to examine, identify, and quantify the factors behind Africa's high prices for road transport. Such prices are a major obstacle to economic growth in the region, as shown in several studies. For example, Amjadi and Yeats (1995) concluded that transport costs in Africa were a higher trade barrier than were import tariffs and trade restrictions. Other analyses by the World Bank (2007a) demonstrated that Africa's transport prices were high compared to the value of the goods transported and that transport predictability and reliability were low by international standards. This study's findings should help policy makers take actions that will reduce transport costs to domestic and international trade.